2016
DOI: 10.1002/ece3.2460
|View full text |Cite
|
Sign up to set email alerts
|

Phenological asynchrony between host plant and gypsy moth reduces insect gut microbiota and susceptibility to Bacillus thuringiensis

Abstract: The phenological synchrony between the emergence of overwintering herbivorous insects and the budding of host plants is considered a crucial factor in the population dynamics of herbivores. However, the mechanisms driving the interactions between the host plant, herbivores, and their pathogens are often obscure. In the current study, an artificially induced phenological asynchrony was used to investigate how the asynchrony between silver birch Betula pendula and gypsy moth Lymantria dispar affects the immunity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 64 publications
1
22
1
Order By: Relevance
“…Phenology can drive these relationships in similar ways as with multicellular natural enemies, as insect immunity can vary with host plant synchrony (Martemyanov et al 2015). The study of mycorrhizae (e.g., Tao et al 2016), phylloplane flora (e.g., Leong et al 1997), midgut biota (e.g., Mason and Raffa 2014;Martemyanov et al 2016), and pathogens (e.g., Hajek et al 1990;Leong et al 1997;van Frankenhuyzen et al 2007;Gowler et al 2015) in plant-herbivore systems is suggesting potentially important roles for multitrophic interactions with these poorly understood organisms. These relationships are only beginning to be identified and their phenologies or responses to climate have yet to be examined.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Phenology can drive these relationships in similar ways as with multicellular natural enemies, as insect immunity can vary with host plant synchrony (Martemyanov et al 2015). The study of mycorrhizae (e.g., Tao et al 2016), phylloplane flora (e.g., Leong et al 1997), midgut biota (e.g., Mason and Raffa 2014;Martemyanov et al 2016), and pathogens (e.g., Hajek et al 1990;Leong et al 1997;van Frankenhuyzen et al 2007;Gowler et al 2015) in plant-herbivore systems is suggesting potentially important roles for multitrophic interactions with these poorly understood organisms. These relationships are only beginning to be identified and their phenologies or responses to climate have yet to be examined.…”
Section: Discussionmentioning
confidence: 99%
“…Recent work shows that late-emerging insects that are limited to feeeding on mature foliage (which contains higher tannin levels) are more susceptible to nuclear polyhedrosis virus (Martemyanov et al 2015) but less susceptible to Bacillus thuringiensis infection (Martemyanov et al 2016). The underlying mechanisms are not understood but could be related to effects on midgut biota: late-emerging larvae show dramatic decreases in the diversity of the midgut bacterial community (Martemyanov et al 2016). The relationship between pathogens and foliar chemistry, notably phenology and induced defenses following defoliation, in their effects on gypsy moth outbreak dynamics remains difficult to establish (Cory and Hoover 2006).…”
Section: Gypsy Mothmentioning
confidence: 99%
“…The previous study suggested that intestinal microflora was involved in human's physical and mental health (Petersen, Skov, Thyssen, & Jensen, ; Stricoff & Robinson, ). Similarly, intestinal microflora plays diverse functions in invertebrate, such as olfactory behavior regulation (Qiao, Keesey, Hansson, & Knaden, ), metabolism (Ayayee, Muñoz‐Garcia, & Keeney, ; B. Chen et al, ), and immune (Lee, Lee, & Lee, ; Martemyanov et al, ; Xia et al, ). In addition, consistent changes of gut microbial community and host development indicated that the gut microbiota might be involved in the entomic development (B. Chen et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Polenogova, unpublished). In other experiments, we demonstrated that the diversity of bacteria in the L. dispar midgut was decreased by the consumption of low-quality leaves and was associated with a decrease in the susceptibility of the insects to the entomopathogenic bacterium B. thuringiensis [23].…”
Section: Interactions Between Parasites and Host Microbial Communitiesmentioning
confidence: 69%